علاقة المرونة النفسية بالصمود الأكاديمي لدى تلاميذ السنة ثالثة ثانوي - بوهلال إيمان; شريط كوثر (My University, 2024)
هدفت الدراسة الحالية إلى التعرف على العلاقة بين المرونة النفسية والصمود الأكاديمي لدى عينة من تلاميذ السنة الثالثة ثانوي بمدينة الوادي، ودراسة الفروق بينهم في المرونة النفسية والصمود الأكاديمي في ضوء متغير التخصص الدراسي. وتكونت عينة الدراسة من (220) تلميذا وتلميذة من تلاميذ ثالثة ثانوي للشعب (علوم تجريبية / آداب وفلسفة) ببعض ثانويات بلدية الوادي تم إختيارهم بطريقة عشوائية طبقية. تم إستخدام المنهج الوصفي الارتباطي وذلك لمناسبته أهداف الدراسة، كما تم إستخدام مقياس المرونة النفسية "كونور دافيدسون" ترجمة هشام عبد الحافظ ربابعة (2018) ومقياس الصمود "كاسيدي" ترجمة نوف بنت سعد بن ساعد اللحياني (2021). توصلت الدراسة إلى وجود علاقة إرتباطيه موجبة متوسطة ذات دلالة إحصائية عند مستوى الدلالة (0.01) بين المرونة النفسية والصمود الأكاديمي، كما توصلت إلى عدم وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0.05) بين متوسطي درجات المرونة النفسية لدى أفراد العينة تعزى لمتغير التخصص الدراسي، كذلك عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05) بين متوسطي درجات الصمود الأكاديمي لدى التلاميذ عينة الدراسة تعزى لمتغير التخصص الدراسي. The current study aimed to identify the relationship between psychological flexibility and academic resilience among third-year secondary school students in the city of El-Wadi and the differences between them in psychological flexibility and academic resilience in light of the academic specialization variable. The study sample consisted of (220) male and female students from third-year secondary school students (experimental sciences / arts and philosophy). In some high schools in the Municipality of the Valley, they were randomly selected. The descriptive, correlational approach was used in order to suit the objectives of the study. The “Connor Davison” psychological flexibility scale and the “Cassidy” resilience scale were applied. The results of the study found that there is a moderate positive correlation with statistical significance at the significance level (0.01) between psychological flexibility and academic resilience. The results also found that there are no statistically significant differences at the significance level (0.05) between the average scores of the sample members. The study on the resilience scale is due to the variable Academic specialization, as well as the absence of statistically significant differences at the significance level (0.05) between the average scores of the study sample members on the resilience scale due to the academic specialization variable.
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: المرونة النفسية; Flexibilité psychologique; Psychological flexibility; الصمود الأكاديمي; Résilience académique; Academic resilience